Series-Loaded Resonant Converter DC-DC Buck Operating for Low Power - M. F. Omar; H. C. M. Haris (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents the functions of Series-Loaded Resonant Converter (SLRC). Series Loaded Resonant DC-DC converter is a type of soft-switching topology widely known for providing improved efficiency. Zero voltage switching (ZVS) buck converter is more preferable over hard switched buck converter for low power, high frequency DC-DC conversion applications. Zero Voltage switching techniques will be used to improve the efficiency of current and voltage at the series loaded half-bridge rectifier. The results will be described from PSIM simulation, Programming of MATLAB calculation and hardware testing.